CGE Analysis of the Impact of Foreign Direct Investment and Tariff Reform on Female and Male Wages - Latorre, Maria C. (World Bank Group, Washington, DC, 2014)
This study analyzes the impact on male and female wages of tariff reform and the reduction of regulatory barriers faced by domestic and foreign firms operating in business services. The study applies the model to Tanzania and develops a data set that distinguishes labor and wages by gender for 52 sectors and four skill categories. The model is the first to incorporate modern trade theory to assess the gender implications of trade reform. Given that the Dixit-Stiglitz framework results in productivity gains from additional varieties of services, the analysis finds that real wages increase across all worker categories. However, the increase in wages is higher for males than for females, because business services use males more intensively than females. The most skilled (female and male) workers, who are also the most intensively used in the business services sectors, benefit more from the real increases in wages. The model illustrates that as the development process continues and developing countries become more business service oriented, these sectors demand more educated workers and their wages will increase relative to those of unskilled workers. The policy conclusion from this model is that it is crucial to invest in the education of females so their human capital increases and their skills are more marketable in business services and other more technologically modern occupations. Otherwise, the wage gap between males and females would likely widen further.